Model Tes Bakat Calon Atlet Sepakbola Untuk KU 9-10 Tahun - Endarman Saputra; Reza Hadinata (Universitas Negeri Medan, 2017)
This research aims to develop a model of basic skill test for talent scouting soccer athlete candidates of age group of 10-11 years which is valid and reliable. This research is research and development adapting research measures proposed by Borg and Gall (2007: 590) including: (1) introductory study and data collection, (2) planning and conducting research, (3) product validation, (4) trying out of the product, (5) revisions of the product, and (6) product implementation. The try out of the initial product was conducted to 30 students. The try out of the main product was conducted to 416 students from various elementary schools (SD) sampled using the cluster sampling technique. The data validity is calculated using with Pearson’s Product Moment correlation and the reliability was calculated using the test-retest of Cronbach's Alpha. The Z score was used to equalize the form of units. The results of this research and development include a model of basic skill test for talent scouting soccer athlete candidates of age group of9-10 years. The talent test model is fit for use, because it is valid and reliable, with the raccount score bigger than rtabelscore. The model of basic skill test for talent scouting soccer athlete candidates of age group of 9-10 years includes the assessment scales (norms) that are packed in the effective and efficient guidebook (module) and visualization/tutorial tests (CD) that can be used as a manual of the soccer academy coaches in the process of scouting prospective athletes with different levels of talent.